Pemphigus—A Disease of Desmosome Dysfunction Caused by Multiple Mechanisms - Spindler, Volker; Waschke, Jens (Frontiers in Immunology, 2018)
Pemphigus is a severe autoimmune blistering disease of the skin and mucous membranes caused by autoantibodies reducing desmosomal adhesion between epithelial cells. Autoantibodies against the desmosomal cadherins desmoglein (Dsg) 1 and 3 as well as desmocollin (Dsc) 3 were shown to be pathogenic whereas the role of other antibodies is unclear. Dsg3 interactions can be directly reduced by specific autoantibodies. Autoantibodies also alter the activity of signalling pathways, some of which regulate cell cohesion under baseline conditions and alter the turnover of desmosomal components. These pathways include Ca2+, p38MAPK, PKC, Src, EGFR/Erk and several others. In this review, we delineate the mechanisms relevant for pemphigus pathogenesis based on the histology and the ultrastructure of patients’ lesions. We then dissect the mechanisms which can explain the ultrastructural hallmarks detectable in pemphigus patient skin. Finally, we re-evaluate the concept that the spectrum of mechanisms which induce desmosome dysfunction upon binding of pemphigus autoantibodies finally defines the clinical phenotype.